DEMOGRAPHICS, KNOWLEDGE AND SMOKING: AN INSTRUMENTAL VARIABLE APPROACH (Journal of Business Management and Accounting, 2021)
Smoking is one of the main factors that causes various diseases. The objective of the present study is to investigate factors determining smoking behaviour among adults. The present study used instrumental variable (IV) regressions to estimate the effects of demographic and knowledge factors on participation decision and amount decision of smoking. Nationally representative data of a developing country (Malaysia) was used. Contrary to popular belief, knowledge was found to be positively associated with the propensity to smoke, as well as the amount of smoking. Age, gender, wealth index, educational 2 Journal of Business Management and Accounting, Vol. 11, Number 2 (July) 2021, pp: 1–24 level, ethnicity, marital status and house locality were significantly associated with smoking. Males were more likely to smoke and smoked more than females. Educational level reduced the likelihood and amount of smoking. Malays and married individuals were less likely to smoke than non-Malays and unmarried individuals. Urban dwellers smoked more cigarette relative to rural dwellers. In terms of policy implication, it is suggested that intervention measures directed toward reducing the prevalence of smoking should not pay too much attention to improving the knowledge of health effects of smoking among Malaysian adults. Anti-smoking policies must be designed carefully by taking into account of the demographic factors which are correlated with the likelihood and amount of smoking. The present study is the first of its kind that includes knowledge as a separate variable for analyses and uses IV regressions to analyse participation decision and amount decision of smoking.